A Rapid, Sensitive, and Portable Biosensor Assay for the Detection of Botulinum Neurotoxin Serotype A in Complex Food Matrices - Christina C. Tam; Andrew R. Flannery; Luisa W. Cheng (Toxins, 2018)
Botulinum neurotoxin (BoNT) intoxication can lead to the disease botulism, characterized by flaccid muscle paralysis that can cause respiratory failure and death. Due to the significant morbidity and mortality costs associated with BoNTs high toxicity, developing highly sensitive, rapid, and field-deployable assays are critically important to protect the nation’s food supply against either accidental or intentional contamination. We report here that the B-cell based biosensor assay CANARY® (Cellular Analysis and Notification of Antigen Risks and Yields) Zephyr detects BoNT/A holotoxin at limits of detection (LOD) of 10.0 ± 2.5 ng/mL in assay buffer. Milk matrices (whole milk, 2% milk and non-fat milk) with BoNT/A holotoxin were detected at similar levels (7.4⁻7.9 ng/mL). BoNT/A complex was positive in carrot, orange, and apple juices at LODs of 32.5⁻75.0 ng/mL. The detection of BoNT/A complex in solid complex foods (ground beef, smoked salmon, green bean baby puree) ranged from 14.8 ng/mL to 62.5 ng/mL. Detection of BoNT/A complex in the viscous liquid egg matrix required dilution in assay buffer and gave a LOD of 171.9 ± 64.7 ng/mL. These results show that the CANARY® Zephyr assay can be a highly useful qualitative tool in environmental and food safety surveillance programs.